Peran Dan Fungsi Public Relation Dalam Mempertahankan Citra Positif Portal Berita Online Antaranews.Com - Dede Mercy Rolando; Tri Adellia; Nuril Maulana Alifia Aziz; Galuh Dwi Kartika Wicaksono (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2021)
This study aims to determine how the role and function of Public Relations in LKBN ANTARA Bureau Lampung in maintaining a positive image in the eyes of the public. In order to examine this research, the author uses descriptive qualitative research methods with data collection in the form of interviews, documentation and literature. The subject of this research is Public Relations practitioners in LKBN Anatara Lampung bureau. This study looks at the impact of technological advances that have disrupted conventional mass media, so that news channels are now converged into online channels. However, due to the convenience offered by online media, the information submitted cannot be filtered properly. The amount of information that is anonymous has resulted in the largest number of hoax news in online media. This reduces the credibility of an online news portal in the eyes of the public. Even some people doubt the accuracy of the news available on online channels. Public Relations at LKBN ANTARA Bureau Lampung acts as a Communication Technician, Communication Facilitator and Problem Solving Facilitator. And Public Relations here also acts as a management function and communication function.